The RIT1 C-terminus associates with lipid bilayers via charge complementarity. (April 2021) - Migliori, Amy D.; Patel, Lara A.; Neale, Chris
Graphical abstract: Highlights: The RIT1 C-terminus is intrinsically disordered. RIT1 uses cationic and hydrophobic residues to bind anionic lipids. Regulatory phosphorylation occurs in the middle of the membrane binding region. Cancer-associated A192 T mutation has no obvious effect on membrane binding. Abstract: RIT1 is a member of the Ras superfamily of small GTPases involved in regulation of cellular signaling. Mutations to RIT1 are involved in cancer and developmental disorders. Like many Ras subfamily members, RIT1 is localized to the plasma membrane. However, RIT1 lacks the C-terminal prenylation that helps many other subfamily members adhere to cellular membranes. We used molecular dynamics simulations to examine the mechanisms by which the C-terminal peptide (CTP) of RIT1 associates with lipid bilayers. We show that the CTP is unstructured and that its membrane interactions depend on lipid composition. While a 12-residue region of the CTP binds strongly to anionic bilayers containing phosphatidylserine lipids, the CTP termini fray from the membrane allowing for accommodation of the RIT1 globular domain at the membrane-water interface.